A model for universal social security coverage: The experience of the BRICS countries. (July 2015) - Ghai, Mridula
Abstract: The BRICS countries have made important progress in extending social security coverage. However, much remains to be achieved to realize the goal of comprehensive universal social security protection. Using policy experiences from the BRICS, the article explores the possibility of drawing from existing models of social security provision to design effective policy interventions for universalizing social security. Main principles of a framework for bridging the coverage gap are identified. These principles are then placed in complimentary and supplementary relationships to develop a framework for policy interventions to bridge the social security coverage gap and achieve universal social security.